#### Answer

$\alpha$=$\frac{\omega-\omega_0}{t}$

#### Work Step by Step

$\omega$=$\omega$$_0$+$\alpha$t
$\alpha$t=$\omega$-$\omega$$_0$
$\alpha$=$\frac{\omega-\omega_0}{t}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$\alpha$=$\frac{\omega-\omega_0}{t}$

$\omega$=$\omega$$_0$+$\alpha$t
$\alpha$t=$\omega$-$\omega$$_0$
$\alpha$=$\frac{\omega-\omega_0}{t}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.